Segmental Darier disease. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2022)
Darier disease is an autosomal dominant inherited skin disorder. The disease is caused by mutations in a gene – ATP2A2 – that encodes a protein involved in the calcium pump. The consequent defect of Ca ions at the level of the desmosomes compromises the desmosomal bonds of the keratinocytes with consequent acantholysis. The disease often manifests itself at puberty and this fact, together with variations in the activity of the disease in conjunction with menstruation, pregnancy, contraceptive use and menopause has led to hypothesize a role for hormones (6). The reporting in the literature of cases of Darier disease associated with neuropsychiatric disorders (3) could be explained by the importance of the calcium pump in the transmission of nerve stimuli. Clinically, Darier’s disease is included in the follicular keratosis group and is characterized by persistent follicular papules in seborrheic sites of the head, neck and trunk that worsen with exposure to ultraviolet rays and heat. Histologically, the disease is characterized in the epidermis by suprabasal lacunae, isolated keratinocytes with morphological alterations (round bodies) and dyskeratosis (grains); these alterations often surround the follicular outlets but are also found in the extrafollicular area. In the literature there are numerous reports (2, 5) of nevi, often of late onset, which have the same clinical manifestations and the same histological changes as Darier’s disease and it has been asked whether to consider them as nevi in their own right or as segmental forms of Darier disease. The demonstration that in the skin affected by these nevi and only in it were present the same mutations of the gene responsible for inherited Darier disease led to the conclusion that they are segmental forms of Darier disease linked to post-zygotic mutations of the same gene (1, 4). In our experience, segmental forms of Darier disease are significantly more frequent than segmental forms of other inherited diseases with autosomal dominant inheritance such as neurofibromatosis.